2008
DOI: 10.1002/j.2051-3909.2008.tb00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Does biplane imaging reduce contrast load, procedural and screening time compared to single‐plane imaging in routine diagnostic coronary angiography?

Abstract: IntroductionDiagnostic coronary angiography utilises radiographic contrast media to delineate epicardial coronary lesions and assess left ventricular function. While contrast media is essential for the radiographic visualisation of coronary vessels, there are certain risks and complications associated with its use. One such complication is contrast-induced nephropathy (CIN). CIN is a life-threatening dose-dependent reaction and is commonly defined as a decrease in renal function 24-48 hours after contrast medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Unsurprisingly, biplane imaging was demonstrated to significantly increase high P KA and OD rates. Biplane imaging uses an additional C‐arm and X‐ray source to acquire images and it has previously been demonstrated to increase FT, DA and P KA . The study by Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, biplane imaging was demonstrated to significantly increase high P KA and OD rates. Biplane imaging uses an additional C‐arm and X‐ray source to acquire images and it has previously been demonstrated to increase FT, DA and P KA . The study by Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of biplane equipment was assumed to be a practical measure to significantly reduce contrast load when compared with single-plane equipment [1, 5-7, 12, 18, 23]. The study by Sadick et al [14] reported a small but significant reduction in contrast load with biplane imaging, compared with single-plane imaging, in a much larger group of patients undergoing diagnostic coronary angiography. This study showed that there was a small but non-significant reduction in contrast load with biplane imaging (BP: 166.8¡62.9 ml vs SP: 176.8¡66.0 ml, p50.052).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study comparing biplane and single-plane imaging in 1156 diagnostic coronary angiography procedures found a small, but notable, reduction in contrast load accompanied by significantly longer table times and screening times with biplane imaging, although radiation dose was not examined [14].…”
mentioning
confidence: 97%
“…A previous study showed bi‐plane imaging resulted in a greater radiation dose and a longer procedural time and delivered a non‐significant reduction in contrast load than single‐plane imaging . Another study comparing bi‐plane and single‐plane imaging in diagnostic coronary angiography procedures found a small, but notable, reduction in contrast load accompanied by significantly longer procedural time with bi‐plane imaging . These findings did not support the commonly perceived advantages of using bi‐plane imaging in diagnostic angiography and simple coronary intervention procedures.…”
Section: Introductionmentioning
confidence: 87%